GAME EDUKASI DUA DIMENSI PENGENALAN HEWAN BERDASARKAN CARA BERKEMBANGBIAKNYA - Ngakan Putu Darma Yasa; Ni Kadek Nita Noviani Pande (Universitas Negeri makassar, 2021)
This research aims to produce learning media in the form of educational games. This educational game can be filled with learning content needed by children so as to provide new learning alternatives. The stages in this research start from collecting data by observation method, interview, documentation and literature. Game design through several stages, namely pre-production, production and post-production. Educational games designed to contain animal recognition materials based on how to breed. Animals featured in the game are animals that are often found everyday such as chickens, rabbits and elephants. Desktop-based educational games mean they can only be played on a computer.